Early-stage Mycosis Fungoides: Epidemiology and Prognosis - Andrew Maguire; Jorge Puelles; Patrick Raboisson; Rajeev Chavda; Sylvie Gabriel; Susan Thornton (Medical Journals Sweden, 2020)
Most patients with mycosis fungoides are diagnosed with early-stage disease. However, prevalence of early-stage disease is unknown, and evidence of its burden is scarce. The aim of this study is to estimate the prevalence of early-stage mycosis fungoides, how long patients live with early-stage disease and to characterise these patients. Data were obtained from 4 key publications and from US cancer registries (Surveillance, Epidemiology and End Results Program; SEER). The derived incidence of early-stage mycosis fungoides was 0.26/100,000 (UK), 0.29/100,000 (US) and 0.38/100,000 (US-SEER) and the prevalence was 4.8/100,000 (UK), 5.2/100,000 (US) and 6.6/100,000 (US-SEER). Early-stage disease may last for 18 years. From SEER registries, 3,132 were diagnosed at early stage (mostly stage IA). Median age at diagnosis was 58 years. Compared with stage IA, the relative risk of death was 1.3 for stage IB and 3.5 for stage IIA. We confirm the rarity of early-stage mycosis fungoides, a differential prognosis and the potential for elevated burden of disease.